A Novel Polyphenol Oxidoreductase OhLac from Ochrobactrum sp. J10 for Lignin Degradation - Yang, Chenxian; Ma, Lingling; Wang, Xin; Xing, Yuqi; Lü, Xin (Frontiers in Microbiology, 2021)
Identifying the enzymes involved in lignin degradation by bacteria is important in studying lignin valorization to produce renewable chemical products. In this paper, the catalytic oxidation of lignin by a novel multi-copper polyphenol oxidoreductase (OhLac) from the lignin degrader Ochrobactrum sp. J10 was explored. Following its expression, reconstitution, and purification, a recombinant enzyme OhLac was obtained. The OhLac enzyme was characterized kinetically against a range of substrates, including ABTS, guaiacol, and 2,6-DMP. Moreover, the effects of pH, temperature, and Cu2+ on OhLac activity and stability were determined. GC-MS results indicated that the β-aryl ether lignin model compound GGE was oxidized by OhLac to generate guaiacol and vanillic acid. Molecular docking analysis of GGE and OhLac was then used to examine the significant amino residues and hydrogen bonding sites in the substrate-enzyme interaction. Altogether, we were able to investigate the mechanisms involved in lignin degradation. The breakdown of the lignocellulose materials wheat straw, corn stalk, and switchgrass by the recombinant OhLac was observed over 3 d and the degradation results revealed that OhLac plays a key role in lignin degradation.